Enhanced biomass production and nutrient removal efficiency from urban wastewater by chlorella pyrenoidosa in batch bioreactor system: Optimization and model simulation - Singh V.; Mishra V. (My University, 2025)
Tertiary wastewater treatment by microalgae has been focused on various researches due to its immense potential of remediating toxic pollutants and the production of valuable biomass. The treatment efficiency is greatly influenced by environmental parameters. In the present work, response surface methodology has been employed to predict the optimum conditions of temperature, pH, and photoperiod for maximizing biomass production and nutrient removal efficiency. The optimum conditions have been calculated as 20.65°C temperature, pH 7.72, and 15.69 h photoperiod. Under the optimum conditions, 5.36 g L–1 of biomass concentration, 98.72% of ammonium nitrogen, and 76.29% of phosphate phosphorus removal efficiency has been obtained by conducting in 2 L Erlenmeyer flask. Various sigmoidal growth and substrate removal kinetic models such as logistic, Gompertz, modified Luedeking-Piret model, biomass dependent, and independent substrate removal kinetic models were used to simulate the growth and substrate removal kinetics of microalgae. These models were compared using the coefficient of regression (R2 ), adjusted R2 (Adj. R2 ), second-order Akaike information criterion, and root mean square error. By comparing the statistical data, it was concluded that the logistic growth model and Luedeking-Piret substrate removal model provided a better fit for the experimental data. Both these models confirmed that the substrate removal by microalgae from wastewater is directly linked to the biomass concentration of the growth of microalgae. © 2020 Desalination Publications. All rights reserved.